A new history of the Church in Wales : governance and ministry, theology and society / edited by Norman Doe. - Doe, Norman (Cambridge University Press, 2020)
This book marks the centenary of the Church in Wales, following its disestablishment in 1920. Part I provides a historical overview: from the Age of the Saints to Victorian times; the disestablishment campaign; Christianity in Wales since 1920; and broad issues faced over the century. Part II explores the constitution, bishops and archbishops, clergy, and laity. Part III examines doctrine, liturgy, rites of passage, and relations with other faith communities. Part IV deals with the church and culture, education, the Welsh language, and social responsibility. Part V discusses the changing images of the Church and its future. Around themes of continuity and change, the book questions assumptions about the Church, including its distinctive theology and Welshness, ecumenical commitment, approach to innovation, and response to challenges posed by the State and wider world in an increasingly pluralist and secularised Welsh society over the century.